High soluble Fas and soluble Fas Ligand serum levels before stent implantation are protective against restenosis - Katsaros, Katharina M.; Wiesbauer, Franz; Speidl, Walter S.; Kastl, Stefan P.; Huber, Kurt; Zorn, Gerlinde; Niessner, Alexander; Glogar, Dietmar; Maurer, Gerald; Wojta, Johann (Thrombosis and Haemostasis, 2011)
Percutaneous coronary intervention (PCI) represents the most important treatment of coronary artery stenosis today. But instent restenosis (ISR) is a limitation for the outcome. Fas and Fas Ligand have been implicated in apoptosis and vessel wall inflammation. Their role in ISR is not known so far. In this prospective study we studied 137 patients with stable coronary artery disease who underwent elective PCI. Blood samples were taken directly before and 24 hours after PCI. Soluble (s)Fas and sFas Ligand serum levels were measured by ELISA. Restenosis was evaluated six to eight months later either by coronary angiography or by exercise testing. During the follow-up period, 18 patients (13%) developed ISR. At baseline, patients with ISR had significantly lower median sFas, as well as sFas Ligand levels compared to patients without ISR (sFAS: ISR 492 pg/ml, no ISR 967 pg/ml, p=0.014; sFAS Ligand: ISR: 26 pg/ml, no ISR: 42 pg/ml, p=0.001). After PCI median sFas levels significantly decreased in patients with ISR compared to patients without ISR [ISR: –152 pg/ml (IQR –36 to –227), no ISR: –38 pg/ml (IQR –173 to +150 pg/ml), p=0.03]. sFas Ligand levels after PCI significantly increased in ISR patients compared to patients without ISR [ISR: 14 pg/ ml (IQR –3 to +26 pg/ml), no ISR –6 pg/ml (IQR –22 to +21 pg/ml), p=0.014]. In conclusion, sFas and sFas Ligand seem to be associated with the development of ISR. Determination of serum levels before and after PCI might help identifying patients at higher risk of ISR.
Keywords: Inflammation; restenosis; stent